Impact of hydrated lime co-additives on nitrogen conservation during livestock waste composting - Bang, Donggyu; Chung, Woojin; Yun, JinJu; Shim, Jeahong; Jeon, Byong-Hun; Zainudin, Mohd Huzairi Mohd; Dowlath, Mohammed Junaid Hussain; Ravindran, Balasubramani (Springer Science and Business Media B.V., 2025)
Nitrogen loss during the composting process is a great challenge that can lead to environmental pollution and reduce compost quality. Lime is often added to the composting mixture to increase the pH, speed-up the decomposition process, and lower the release of toxic gases like ammonia. However, the specific effects of lime on nitrogen dynamics, particularly ammoniacal nitrogen and nitrate nitrogen levels, as well as CO2 emissions, remain areas of active investigation. This study investigates the influence of hydrated lime on nitrogen conservation when added to poultry manure and agricultural waste. To evaluate the level of nitrogen retention and overall compost stability, poultry waste and agricultural waste were co-composted with and without hydrated lime amendment under controlled environmental conditions. The results showed that, in comparison to the control, the lime-treated compost had higher nitrate nitrogen levels (1800 mg/kg) and lower ammoniacal nitrogen levels (100 mg/kg), indicating improved nitrogen retention. Furthermore, CO2 emissions in the compost treated with hydrated lime were higher in the early phases, however substantially dropped as the compost matured, indicating a faster stabilization process. The findings of 16 S rRNA sequencing showed that lime-treated composting was dominated by Thermobifida, Thermobacillus, and Saccharomonospora, all of which were known as cellulolytic bacteria and involved in organic matter degradation. Also, significant bacterial shifts were observed during the thermophilic phase. The Pseudomonas population, which is often associated with the denitrification process, was lower than the control, thus, promoting nitrogen retention. The results imply that lime amendment improves composting stability and quality by increasing nitrogen content while reducing organic matter. This work advances the understanding and knowledge on the influence of lime in composting by providing useful insights into the microbial community that can be used for improving the process. © The Author(s), under exclusive licence to Springer Nature B.V. 2025.